Uganda : Country Procurement Assessment Report, Volume 3. Annexes - World Bank (Washington, DC, 2013)
The main objective of this 2004 Country Procurement Assessment Report (CPAR) for Uganda is to update the 2001 CPAR, the basis for the ongoing procurement reforms, to incorporate lessons learned and the changing role of donors in their fiduciary oversight resulting from the shift of focus from project lending to program lending. This updated CPAR covers the issues related to weaknesses in the existing legal and institutional frameworks and capacity building. The CPAR has identified four key areas the Government needs to focus on as a matter of priority to ensure Uganda's procurement system achieves maximum positive impact in promoting economy, efficiency, transparency and accountability. The four areas are : weaknesses in local government procurement; weak compliance and enforcement quandary; weak capacity dilemma; and apparent abdication by the Ministry of Finance of its policy making and coordination roles in procurement. Addressing these four issues will go a long way towards achieving the second generation procurement reforms proposed in this CPAR.